2016
DOI: 10.1371/journal.pone.0160527
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Prognostic Effect of E-Cadherin Expression in Colorectal Signet Ring Cell Carcinoma

Abstract: PurposeSignet ring cell carcinoma (SRCC) is rare. The aim of this study is to understand the clinicopathological features and identify the possible prognostic factors in colorectal SRCC.MethodsPatients with SRCC who underwent primary lesion resection at Fudan University Shanghai Cancer Center from September 2008 to July 2014 were retrospectively analyzed. Patient’s gender, age, tumor location, depth of invasion, lymph node metastasis, synchronous distant metastasis, perineural invasion, lymphovascular invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
(36 reference statements)
2
25
0
Order By: Relevance
“…In agreement with previous colorectal SRCC data, 4 , 5 , 7 9 colorectal MAC-SRC patients were commonly diagnosed at an advanced stage in this study, with distant metastasis or lymph node metastasis. In a previous study examining 59 patients, 58 (98.3%) individuals had T3/T4 lesions, 52 (88.1%) showed lymph node metastasis, and 14 (23.7%) had distant metastasis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous colorectal SRCC data, 4 , 5 , 7 9 colorectal MAC-SRC patients were commonly diagnosed at an advanced stage in this study, with distant metastasis or lymph node metastasis. In a previous study examining 59 patients, 58 (98.3%) individuals had T3/T4 lesions, 52 (88.1%) showed lymph node metastasis, and 14 (23.7%) had distant metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study examining 59 patients, 58 (98.3%) individuals had T3/T4 lesions, 52 (88.1%) showed lymph node metastasis, and 14 (23.7%) had distant metastasis. 5 In line with previous reports, almost all cases (96.3%) in the current study were diagnosed as stage T3 or T4, with 91.4% and 29.3% showing lymph node involvement and distant metastasis, respectively. Early diagnosis might be challenging because colorectal MAC-SRC is merely asymptomatic in the initial stage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yang et al [13] have suggested that patients with in-frame fusion genes containing the RhoGAP domain represent the aggressive subset of DGCs. Wang et al [30] have suggested that loss of E-cadherin is associated with poor prognosis. However, there is no clear consensus regarding the chemosensitivity and prognosis of cell-adherens junction molecules in mDGCs.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent studies, however, reported that age showed no correlation with survival in patients with colorectal SRCC. Wang et al [24] analyzed 59 patients with colorectal SRCC and found that age (40 years old as cutoff value) was not a prognostic factor for survival. Kakar and Smyrk [25] reported that age (70 years old as cutoff value) was not significantly associated with survival in a study including 72 patients with SRCC of the colorectum.…”
Section: Discussionmentioning
confidence: 99%